The Function of the State in Providing Health Services: Indonesia Perspective - Marif; Nurhaedah; Handar Subhandi Bakhtiar (Institute of Medico-legal Publications Pvt Ltd, 2021)
The function of the state in providing health services is divided into the regulatory function, the controllingfunction, the entrepreneurial function and the supervisory function. In the regulatory function, the statedevelops policies in the field of health services that ensure that all people can enjoy health services. Thestate control function is responsible for the availability of equipment and medicines as well as maintainingthe stability of the flow of health service distribution. In the entrepreneurial function, the state in addition toproviding health services can receive income from health services which can later be used to equalize thecosts of health care dependents, especially for the poor and underprivileged. In the oversight function, thestate is responsible for carrying out full supervision of health facilities in order to optimally provide healthservices to the people.Keywords: State functions, health services, the right to health.